Optimal Control Strategy of Five-Phase PMSMs in a Wide Speed Range Using Third Harmonics - Danyal Ghasemi; Jafar Siahbalaee; Mohammad Divandari (International Transactions on Electrical Energy Systems)
The utilization of the third current harmonic in five-phase motors offers the potential to enhance their performance. This paper presents a comprehensive theory for optimally controlling five-phase permanent magnet synchronous motors (PMSMs) across all speeds, considering both motor and inverter limitations. A three-region speed profile is defined based on motor and inverter constraints, with precise relationships derived for determining region boundaries. Distinct control strategies are proposed for each region: maximum torque per ampere (MTPA) for copper loss minimization and maximum voltage–maximum current (Max V–Max I) and maximum power per voltage (MPPV) for core loss minimization. Optimal components of the first and third current harmonics are calculated for each strategy, serving as reference values for control methods such as FOC, DTC, or MPC in motor drives. Analysis results indicate that the proposed strategies significantly increase electromagnetic torque and output power and decrease power loss of five-phase PMSM motors.